Impact of carbonation on unsaturated water transport properties of cement-based materials. (August 2015) - Auroy, Martin; Poyet, Stéphane; Le Bescop, Patrick; Torrenti, Jean-Michel; Charpentier, Thibault; Moskura, Mélanie; Bourbon, Xavier
Abstract: In unsaturated conditions, the durability of concrete structures is strongly dependent on the evolution of the amount of free water within concrete porosity. Reliable durability assessment of concrete structures in relation to their environment thus requires accurate unsaturated water transport description as well as reliable input data. The effect of carbonation on water transport remains poorly studied and data are lacking. It was then the purpose of this article to acquire all the data needed to describe unsaturated water transport in carbonated cementitious materials (porosity, water retention and unsaturated permeability). Four hardened pastes made with four different binders were carbonated at 3% CO2 to ensure representativeness with natural carbonation. Beyond the modification of the water retention curve and porosity clogging, significant microcracking due to carbonation shrinkage was observed. The consequence on permeability highlighted a competition between porosity clogging and microcracking that was dependent on the initial mineralogical composition.